Prove the following trigonometric equation
$4\cos {12^0}\cos {48^0}\cos {72^0} = \cos {36^0}$
Answer
Verified
509.4k+ views
Hint- Use different trigonometric identities of combination of angles in order to solve the question, also keep in mind the RHS part for manipulation.
Complete step-by-step solution -
Given that: to prove $4\cos {12^0}\cos {48^0}\cos {72^0} = \cos {36^0}$
Since we know that
$2\cos A\cos B = \cos \left( {A + B} \right) + \cos \left( {A - B} \right)$
Taking the LHS part and proceeding further
$
LHS = 4\cos {12^0}\cos {48^0}\cos {72^0} \\
= 2 \times \left( {2\cos {{12}^0}\cos {{48}^0}} \right) \times \cos {72^0} \\
$
With the help of above formula simplifying the middle term
$
= 2 \times \left[ {\cos \left( {{{48}^0} + {{12}^0}} \right) + \cos \left( {{{48}^0} - {{12}^0}} \right)} \right] \times \cos {72^0} \\
= 2 \times \left[ {\cos \left( {{{60}^0}} \right) + \cos \left( {{{36}^0}} \right)} \right] \times \cos {72^0} \\
= 2\cos {60^0}\cos {72^0} + 2\cos {36^0} \times \cos {72^0} \\
$
Now substituting the value of know trigonometric quantity in the above equation
$
= 2 \times \dfrac{1}{2} \times \cos {72^0} + 2\cos {36^0}\cos {72^0}{\text{ }}\left[ {\because \cos {{60}^0} = \dfrac{1}{2}} \right] \\
= \cos {72^0} + 2\cos {36^0}\cos {72^0} \\
$
Again using the formula in second part
$
= \cos {72^0} + \left[ {\cos \left( {{{72}^0} + {{36}^0}} \right) + \cos \left( {{{72}^0} - {{36}^0}} \right)} \right] \\
= \cos {72^0} + \left[ {\cos {{108}^0} + \cos {{36}^0}} \right] \\
$
Also we know that
$
\cos \left( {180 - \theta } \right) = - \cos \theta \\
\Rightarrow \cos {108^0} = \cos \left( {{{180}^0} - {{72}^0}} \right) = - \cos {72^0} \\
$
So, substituting the value in above equation we have
$
= \cos {72^0} + \cos {108^0} + \cos {36^0} \\
= \cos {72^0} - \cos {72^0} + \cos {36^0}{\text{ }}\left[ {\because \cos {{108}^0} = - \cos {{72}^0}({\text{proved above}})} \right] \\
= \cos {36^0} \\
$
Which is equal to the RHS.
Hence, the given trigonometric equation is proved.
Note- In order to solve types of complex problems including some random angle values always try to use the trigonometric identities in order to solve the problem. Never try to find the value of such trigonometric terms. Whenever while solving if some known values of trigonometric terms appear, put into the values of such terms. Also keep in mind the part to be proved for an easy solution.
Complete step-by-step solution -
Given that: to prove $4\cos {12^0}\cos {48^0}\cos {72^0} = \cos {36^0}$
Since we know that
$2\cos A\cos B = \cos \left( {A + B} \right) + \cos \left( {A - B} \right)$
Taking the LHS part and proceeding further
$
LHS = 4\cos {12^0}\cos {48^0}\cos {72^0} \\
= 2 \times \left( {2\cos {{12}^0}\cos {{48}^0}} \right) \times \cos {72^0} \\
$
With the help of above formula simplifying the middle term
$
= 2 \times \left[ {\cos \left( {{{48}^0} + {{12}^0}} \right) + \cos \left( {{{48}^0} - {{12}^0}} \right)} \right] \times \cos {72^0} \\
= 2 \times \left[ {\cos \left( {{{60}^0}} \right) + \cos \left( {{{36}^0}} \right)} \right] \times \cos {72^0} \\
= 2\cos {60^0}\cos {72^0} + 2\cos {36^0} \times \cos {72^0} \\
$
Now substituting the value of know trigonometric quantity in the above equation
$
= 2 \times \dfrac{1}{2} \times \cos {72^0} + 2\cos {36^0}\cos {72^0}{\text{ }}\left[ {\because \cos {{60}^0} = \dfrac{1}{2}} \right] \\
= \cos {72^0} + 2\cos {36^0}\cos {72^0} \\
$
Again using the formula in second part
$
= \cos {72^0} + \left[ {\cos \left( {{{72}^0} + {{36}^0}} \right) + \cos \left( {{{72}^0} - {{36}^0}} \right)} \right] \\
= \cos {72^0} + \left[ {\cos {{108}^0} + \cos {{36}^0}} \right] \\
$
Also we know that
$
\cos \left( {180 - \theta } \right) = - \cos \theta \\
\Rightarrow \cos {108^0} = \cos \left( {{{180}^0} - {{72}^0}} \right) = - \cos {72^0} \\
$
So, substituting the value in above equation we have
$
= \cos {72^0} + \cos {108^0} + \cos {36^0} \\
= \cos {72^0} - \cos {72^0} + \cos {36^0}{\text{ }}\left[ {\because \cos {{108}^0} = - \cos {{72}^0}({\text{proved above}})} \right] \\
= \cos {36^0} \\
$
Which is equal to the RHS.
Hence, the given trigonometric equation is proved.
Note- In order to solve types of complex problems including some random angle values always try to use the trigonometric identities in order to solve the problem. Never try to find the value of such trigonometric terms. Whenever while solving if some known values of trigonometric terms appear, put into the values of such terms. Also keep in mind the part to be proved for an easy solution.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE